The role of mechanical pressure on dendritic surface toward stable lithium metal anode. (November 2020) - Qin, Liguang; Wang, Kehua; Xu, Hui; Zhou, Min; Yu, Genxi; Liu, Changfeng; Sun, Zhengming; Chen, Jian
Abstract: The lithium dendrites have traditionally been thought as one of the main causes for the failure of high-energy-density lithium metal batteries. Although many strategies have been proposed to suppress the dendrite growth, there are few effective ones to modulate the lithium metal anode itself. In this study, the cycled lithium foils with free growing dendrites are used as the self-template to construct the unique microscale patterns through mechanical compression. The influences of the unique morphology as well as the generated residual stress during compression process are investigated. It is found that preferential deposition/stripping of lithium in the pores takes place due to the synergistic effects of surface morphology and residual stress field. In turn, the reused lithium electrodes in a symmetric cell exhibit extraordinary cycle stability at a high current density of 5 mA cm −2 with a large depth of discharge of 10 mAh cm −2 . The half-cell paired with Li4 Ti5 O12 also delivers superior rate capability. The facile and efficient mechanical strategy demonstrates that the residual stress field need be considered as a new design factor. In addition, the modulation of cycled lithium metal anodes sheds light on the recycle of waste lithium. Graphical abstract: Image 1 Highlights: The cycling performance of the cycled lithium anode (C-Li) was enhanced through a facile mechanical compression method. Synergistic effects of unique pattern and residual stress contribute to the superiority of cycled-compressed Li (PC-Li). The mechanical strategy shows promise for the reuse of waste Li foils.